Novel Cephalosporins in Septic Subjects and Severe Infections: Present Findings and Future Perspective - Corcione, Silvia; Lupia, Tommaso; De Rosa, Francesco Giuseppe (Frontiers in Medicine, 2021)
Cephalosporins have significantly evolved in the past decade, and data regarding novel cephalosporins (i.e., ceftobiprole, ceftaroline, ceftolozane/tazobactam, ceftazidime/avibactam and cefiderocol) within septic and bacteremic subjects are rising. The in vitro microbiological susceptibilities of these compounds are on the whole very promising, although the literature appreciates the variability of susceptibility rates among diverse gram-negative and -positive strains from various countries and cohorts. In addition to these favourable MICs, we need more pharmacological data to assess the best dosage in critically ill patients to avoid subtherapeutic levels of the drugs. These new compounds theoretically permit a sparing approach in various antimicrobial classes, such as aminoglycosides, as well as sparing use in endovascular and GNB bacteremia and colistin- and carbapenem-sparing strategy within the Enterobacteriales infections group, which favours molecules with a good safety profile. Furthermore, novel cephalosporins opening new and exciting prospects in severe infections in the future out of the actual indications. In the future, the desirable approach to sepsis and severe infections will be addressed to the patients according to their clinical situation, the intrinsic host characteristic, the susceptibility profile and local epidemiology trusting that the evidence regarding the use of novel cephalosporins in the treatment of severe infections may fill the gaps that still exist.